Labor Clauses in Trade Agreements: Worker protection or protectionism? - Céline Carrère; Marcelo Olarreaga; Damian Raess (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
We explore the impact on bilateral trade flows of the inclusion of a labor clause (LC) in Trade Agreements (TAs). Using a gravity type framework, we find that the introduction of LCs has on average no impact on bilateral trade flows. However, there is some interesting heterogeneity. Exports of low-income countries benefit from the introduction of LCs in North-South trade agreements. Interestingly, the impact is stronger when accompanied by deep cooperation. On the other hand, stronger enforcement mechanisms, at best, marginally reinforce the impact of LCs. The results are clearly inconsistent with the idea that LC are set for protectionist reasons, casting doubt on the reluctance by low-income countries to include labor clauses in their trade agreements. Key Words: Labor Clause, Free Trade Agreements, Gravity Equation
Keywords: F16; 330; Labor Clause; Free Trade Agreements; Gravity Equation